Prediction and classification performance of reservoir computing system using mutually delay-coupled semiconductor lasers - Hou, Yu-Shuang; Xia, Guang-Qiong; Jayaprasath, Elumalai; Yue, Dian-Zuo; Yang, Wen-Yan; Wu, Zheng-Mao (Optics communications, 2019)
A reservoir computing (RC) system based on two mutually delay coupled semiconductor lasers (MDC-SLs) subject to optical injection is proposed, and the chaotic time series prediction and signal classification performance for such a system is numerically investigated via the Santa-Fe time-series prediction task and the signal classification task, respectively. The simulation results indicate that, when adopting this system to process ultra-fast data with rate up to 1 Gbps, the best prediction error 5.1×10−5±5.2×10−6 and signal recognition error 5.5×10−4±8.8×10−5 can be achieved under optimized operation parameters.